2013
DOI: 10.1371/journal.pone.0068206
|View full text |Cite
|
Sign up to set email alerts
|

The Metastasis Suppressor, N-myc Downregulated Gene 1 (NDRG1), Is a Prognostic Biomarker for Human Colorectal Cancer

Abstract: Metastasis remains to be one of the most prevalent causes leading to poor long-term survival of colorectal cancer (CRC) patients. The clinical significances of tumor metastatic suppressor, N-myc downregulated gene 1 (NDRG1), have been inconsistently reported in a variety of cancerous diseases. In this study with 240 CRC clinical specimens, we showed that NDRG1 expression was significantly decreased in most of CRC tissues compared to the paired non-tumor counterparts. Statistical analysis revealed a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…A variety of studies have shown the important role of NDRG1 in inhibiting cancer cell metastasis (Kovacevic and Richardson, 2006;Liu et al, 2011b;Chen et al, 2012;Liu et al, 2012b;Bae et al, 2013;Mao et al, 2013b;Sun et al, 2013a). However, complete understanding of its mechanism of action remains an important research goal.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have shown the important role of NDRG1 in inhibiting cancer cell metastasis (Kovacevic and Richardson, 2006;Liu et al, 2011b;Chen et al, 2012;Liu et al, 2012b;Bae et al, 2013;Mao et al, 2013b;Sun et al, 2013a). However, complete understanding of its mechanism of action remains an important research goal.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, instead of its suppression role in NPC and several other carcinoma, NDRG1 promotes the development or metastasis of lung cancer [10], colon cancer [12], and hepatocellular carcinomas [17]. One possible explanation for these opposite observations is that NDRG1 may use different signaling pathways in different tumor cells to regulate the tumor cell growth, migration and invasive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NDRG1 plays different roles in different types of tumors. NDRG1 appears to serve as a putative tumor suppressor and is down-regulated in colorectal [11,12], gastric [13], cervical [14], ovarian [15] and prostate [16] cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC was scored in a double-blinded manner by two authors. The German semi-quantitative scoring system, which takes into consideration the staining intensity and percentage of stained cancer cells, was applied to score NEK2 expression [33]. Staining levels were scored as 0 (no staining), 1 (weak staining), 2 (moderate staining), and 3 (strong staining), according to the staining intensity in the tumor cells.…”
Section: Immunohistochemistry (Ihc) and Ihc Evaluationmentioning
confidence: 99%